EFFECT OF GROWTH, YIELD, FORAGE OF OAT (Avena sativa L.) VARIETIES. - Aziz, Moyassar M.; Younis, Salim A. (Diyala Agricultural Sciences Journal, 2013)
This study was conducted in the winter season 2012-2013at Ba'shiqah / Tobzawh village (25 km) east of Mosul and farm of the College of Agriculture and Forestry/ University of Mosul, and both regions are located within the semiarid areas belt where their rain fall ranging from 300-350 mm per year. The study included experiment at each Location to study the effect of sowing rates 120 and 140 kg / ha on growth character, and forage yield of five varieties of oats (ICARDA Tall ,Possum ,Mitika ,Kangaroo and ICARDA Short,) The experiment carried out according to the system of split plot design in Randomized Complete Blok with three replicates The most important results, including the following: Seeding rates 120kg/ha surpass seeding rates 140kg/ha in days from planting to 50% flowering and plant height seeding rate 140kg/ha surpass seeding rate120kg/ha number of tillers/m2 day forage yield and protein percentage dry forage, The leaf percentage seeding rates at both locations Oat Varieties ICARDA Tall, Kangaroo and ICARDA Short surpass and Mitika Varieties dry forage yield and protein percentage at both locations The interaction between seeding rates and Oat Varieties significantly affected all growth characters and dry forage at both location except the number of/tillers / pant at Tabzaioh location.